2010
DOI: 10.1111/j.1528-1167.2010.02698.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence seizures: Individual patterns revealed by EEG‐fMRI

Abstract: SUMMARYPurpose: Absences are characterized by an abrupt onset and end of generalized 3-4 Hz spike and wave discharges (GSWs), accompanied by unresponsiveness. Although previous electroencephalography-functional magnetic resonance imaging (EEG-fMRI) studies showed that thalamus, default mode areas, and caudate nuclei are involved in absence seizures, the contribution of these regions throughout the ictal evolution of absences remains unclear. Furthermore, animal models provide evidence that absences are initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 48 publications
10
125
1
Order By: Relevance
“…These areas connect to cingulate, caudate, putamen, frontal cortex, supplementary motor area, postcentral cortex, and occipital cortex,41 all cortical areas that are associated with GGE 36, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…These areas connect to cingulate, caudate, putamen, frontal cortex, supplementary motor area, postcentral cortex, and occipital cortex,41 all cortical areas that are associated with GGE 36, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…15 Thus, various models of data analysis have helped in understanding epilepsy further, and now there is increasing interest in using these models to reclassify epilepsy as a focal epileptogenic area 10,15 or as a network of seizure-generating areas. [16][17][18] Gower's clinical observation that "seizures beget seizures" in 1881 triggered several studies, especially animal models that addressed the genesis of epilepsy. Kindling is a phenomenon in which the repetition of subconvulsive electrical stimuli results in a progressive epileptic state and an increased frequency of seizures.…”
mentioning
confidence: 99%
“…A consistent cortical site of initiation of SWDs within the perioral region of the somatosensory cortex was demonstrated in rodent absence seizures. High density EEG as well as MEG and fMRI studies in patients with different types of idiopathic generalized epilepsy (IGE) has shown SWDs in discrete, mainly frontal and parietal cortical regions before they appear over the rest of the cortex [101][102][103][104][105][106]. These studies strongly suggest that the frontal lobe is important for the generation of the 3Hz corticothalamic oscillations Do spindles play a role in this new view of IGE?…”
Section: Spindles and Epilepsymentioning
confidence: 97%